ANALISIS PERTUMBUHAN DAN HASIL DUA VARIETAS BUNCIS (Phaseolus vulgaris L.) PADA PERBEDAAN JENIS PUPUK ORGANIK CAIR (The Analysis of Growth and Yield of Two Beans Varieties (Phaseolus Vulgaris L.) at Different Types of Organic Liquid Fertilizer Material) - Made Deviani Duaja (Bioplantae, 2013)
The aim of this research were to determine the best combination between varieties and types of organic liquid fertilizers. This research was conducted at the Teaching and Research Farm Faculty of Agriculture, University of Jambi. The laboratory analysis for liquid organic fertilizer was done ​​in BIOTROP, Bogor. This research used Completely Randomized design (CRD ) with four combination treatments : Tala variety and basic material liquid organic fertilizer Lamtoro, Tala variety and basic material liquid organic fertilizer Kirinyuh, Bayu variety and basic material liquid organic fertilizer Lamtoro, Bayu variety and basic material liquid organic fertilizer Kirinyuh. The result showed that Bayu variety and basic material liquid organic fertilizer Kirinyuh trend gave the highest Leaf Area Duration (DLD), Net Assimilation Rate (NAR), Relative Growth Rate (RGR), number of pods and the yield per plant. Keywords: Liquid ,organic , fertilizer, beans.